Zat Kimia Alami pada Minyak Wangi Bagi Kesehatan dalam Tinjauan Hadis (Pusat Riset dan Inovasi Nasional, 2024)
Perfume has been used since the time of the Prophet Muhammad, not only as a means to improve appearance and cleanliness, but also has spiritual, aesthetic, and health values. The aroma produced from natural ingredients such as flowers, wood, and spices is believed to be able to provide calm and improve the quality of life. This study aims to examine the content of natural chemicals in perfumes, such as essential compounds from plants, and their positive impacts on human physical and mental health. In addition, this study also reviews the use and recommendations of perfumes in the hadiths of the Prophet Muhammad, which show that the use of fragrances is part of an Islamic lifestyle that is sunnah. The method used is a systematic literature review, by examining various scientific sources related to natural chemistry and appropriate hadith books. The results of the study show that several natural compounds such as linalool, eugenol, citronellol, and others have antibacterial, antidepressant effects, and provide a sense of relaxation and comfort. From the perspective of the hadith, the use of perfume is a form of cleanliness, respect for others, and a reflection of noble morals. This study concludes that there is harmony between Islamic values and the scientific benefits of natural chemicals in perfume for physical and mental health.